Retinal and circulating miRNA expression patterns in diabetic retinopathy: An in silico and in vivo approach - Platania, Chiara Bianca Maria; Maisto, Rosa; Trotta, Maria Consiglia; D'Amico, Michele; Rossi, Settimio; Gesualdo, Carlo; D'Amico, Giovanbattista; Balta, Cornel; Herman, Hildegard; Hermenean, Anca; Ferraraccio, Franca; Panarese, Iacopo; et al. (British journal of pharmacology, 2019)
Background and Purpose Diabetic retinopathy, a secondary complication of diabetes mellitus, can lead to irreversible vision loss. Currently, no treatment is approved for early phases of diabetic retinopathy. Modifications of the expression pattern of miRNAs could be involved in the early retinal damage of diabetic subjects. Therefore, we aimed at identification of dysregulated miRNAs–mRNA interactions that might be biomarkers and pharmacological targets for diagnosis and treatment of early diabetic retinopathy. Methods A focused set of miRNAs was predicted through a bioinformatic analysis accessing to Gene Expression Omnibus dataset and enrichment of information approach (GENEMANIA‐Cytoscape). Identification of miRNAs–mRNA interactions was carried out with miRNET analysis. Diabetes was induced in C57BL6J mice by streptozotocin and samples analysed at 5 and 10 weeks after diabetes induction. Retinal ultrastructure of diabetic mice was analysed through electron microscopy. We used Real‐time PCR, western blot analysis, elisa, and immunohistochemistry to study expression of miRNAs and possible targets of dysregulated miRNAs. Key Results We found that miR‐20a‐5p, miR‐20a‐3p, miR‐20b, miR‐106a‐5p, miR‐27a‐5p, miR‐27b‐3p, miR‐206‐3p, and miR‐381‐3p were dysregulated in the retina and serum of diabetic mice. VEGF, brain‐derived neurotrophic factor (BDNF), PPAR‐α, and cAMP response element‐binding protein 1 (CREB1) are targets of dysregulated miRNAs, which then modulated protein expression in diabetic retina. We found structural modifications in retinas from diabetic mice. Conclusions and Implications Serum and retina of diabetic mice express eight dysregulated miRNAs, which modified the expression of VEGF, BDNF, PPAR‐α, and CREB1, before vasculopathy in diabetic retinas.